Plant natriuretic peptides induce proteins diagnostic for an adaptive response to stress - Turek, Ilona; Marondedze, Claudius; Wheeler, Janet I.; Gehring, Chris; Irving, Helen R. (Frontiers in Plant Science, 2014)
In plants, structural and physiological evidence has suggested the presence of biologically active natriuretic peptides (PNPs). PNPs are secreted into the apoplast, are systemically mobile and elicit a range of responses signaling via cGMP. The PNP-dependent responses include tissue specific modifications of cation transport and changes in stomatal conductance and the photosynthetic rate. PNP also has a critical role in host defense responses. Surprisingly, PNP-homologues are produced by several plant pathogens during host colonization suppressing host defense responses. Here we show that a synthetic peptide representing the biologically active fragment of the Arabidopsis thaliana PNP (AtPNP-A) induces the production of reactive oxygen species in suspension-cultured A. thaliana (Col-0) cells. To identify proteins whose expression changes in an AtPNP-A dependent manner, we undertook a quantitative proteomic approach, employing tandem mass tag (TMT) labeling, to reveal temporal responses of suspension-cultured cells to 1 nM and 10 pM PNP at two different time-points post-treatment. Both concentrations yield a distinct differential proteome signature. Since only the higher (1 nM) concentration induces a ROS response, we conclude that the proteome response at the lower concentration reflects a ROS independent response. Furthermore, treatment with 1 nM PNP results in an over-representation of the gene ontology (GO) terms “oxidation-reduction process”, “translation” and “response to salt stress” and this is consistent with a role of AtPNP-A in the adaptation to environmental stress conditions.